Sovereign Rating News and Financial Markets Spillovers : Evidence from the European Debt Crisis - Candelon, Bertrand (IMF Working Papers; Working Paper ;, 2011)
This paper examines the spillover effects of sovereign rating news on European financial markets during the period 2007-2010. Our main finding is that sovereign rating downgrades have statistically and economically significant spillover effects both across countries and financial markets. The sign and magnitude of the spillover effects depend both on the type of announcements, the source country experiencing the downgrade and the rating agency from which the announcements originates. However, we also find evidence that downgrades to near speculative grade ratings for relatively large economies such as Greece have a systematic spillover effects across Euro zone countries. Rating-based triggers used in banking regulation, CDS contracts, and investment mandates may help explain these results.